Method for selective photocatalytic oxidation of thioether compounds into sulfone compounds

By using a metal -non -doped polyitable tubular nitrogen nitride as an optical catalyst, the environmental pollution and side reaction control problems of sulfe ether oxidation are solved, and the method of highly efficient and selectively synthesized pyradic compounds.

CN119371342APending Publication Date: 2025-01-28ZUNYI MEDICAL UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411511987.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art has problems of environmental pollution risks and difficult to control side reactions when preparing sulfoxide in sulfide oxidation.

Method used

Under the optical catalyst, the non-metallic doped porous tubular nitride (B-HTS-400) is used as a photocatalyst, and the sulfe ether is selectively converted into a pyrodhumin compound under mild conditions through the photocatalytic oxidation method.

Benefits of technology

Achieve efficient and selectively synthetic compounds, avoid the use of precious metals and high energy, reduce costs, and improve atomic economy and yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371342A_ABST
    Figure CN119371342A_ABST
Patent Text Reader

Abstract

The invention discloses a method for selective photocatalytic oxidation of a thioether compound into a sulfone compound in the technical field of material chemistry, which comprises the following steps: by taking methyl phenyl sulfide as a substrate, porous tubular carbon nitride (B-HTs-400) as a photocatalyst, and any one or two of an organic solvent and water as a reaction solvent, carrying out selective photocatalytic oxidation on the sulfone compound to obtain the sulfone compound. And synthesizing methyl phenyl sulfoxide as shown in a formula 1b, wherein the synthesis route is as shown in the specification: # imgabs0 #. The method in the scheme can reduce environmental pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material chemistry, and in particular to a method for selectively photocatalytically oxidizing sulfide compounds into sulfone compounds. Background Art

[0002] The study of selective oxidation of sulfides to sulfone compounds is not only a cutting-edge topic in the current field of organic chemistry and chemical synthesis, but also plays an indispensable role in the development of pharmaceutical industry, agricultural chemicals and the wider field of organic synthesis, as sulfoxide compounds are important organic synthesis intermediates and molecular building blocks. With the increasing attention paid to environmental sustainability, finding greener synthetic pathways has become the direction of common efforts of scientific researchers.

[0003] Photocatalytic technology is favored in the field of chemical synthesis due to its mild reaction conditions, environmental friendliness and high efficiency, and is particularly suitable for the selective catalytic oxidation of sulfides. In contrast, the traditional oxidants for the oxidation of sulfides to prepare sulfoxides are mainly strong transition metal oxidants, which usually contain manganese and chromium. However, these traditional oxidants are often accompanied by potential environmental pollution risks during their application, and due to their strong oxidizing properties, they may cause side reactions, making the entire reaction process difficult to accurately control. These problems limit their application in the preparation of fine chemicals, especially pharmaceutical intermediates.

[0004] In view of this, it is particularly important to research and develop a more advanced and efficient catalytic system, preferably one that does not require the use of precious metals or is even completely metal-free and environmentally friendly. Such a catalytic system can not only effectively avoid environmental pollution, but also improve the selectivity and yield of the target product, thereby promoting the development of a green synthesis process for sulfide to sulfone compounds. Summary of the invention

[0005] The present invention aims to provide a method for selectively photocatalytically oxidizing sulfide compounds into sulfone compounds, so as to solve the problem of environmental pollution caused by the prior art.

[0006] In this scheme, a method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds is used, wherein methyl phenyl sulfide shown in formula 1a is used as a substrate, porous tubular carbon nitride (B-HTs-400) is used as a photocatalyst, and any one or two of an organic solvent and water are used as a reaction solvent to synthesize methyl phenyl sulfoxide shown in formula 1b. The synthesis route is as follows:

[0007]

[0008] The working principle and beneficial effects of this scheme: Compared with the prior art, the present invention develops a non-metal-doped porous tubular carbon nitride for the selective photocatalytic oxidation of sulfide compounds to sulfoxides, which effectively avoids the use of precious metals, electricity, and thermal energy, greatly reduces costs, improves atom economy, simplifies the operating steps, and successfully obtains sulfoxide compounds with a yield of 89.6% under mild conditions, which provides a novel idea for the selective synthesis of sulfoxide compounds.

[0009] Furthermore, the porous tubular carbon nitride is boron-doped porous tubular carbon nitride (B-HTs-400).

[0010] Furthermore, the synergistic catalyst is sodium persulfate, and the amount used is 0 to 5 eq to synthesize the methyl phenyl sulfone shown in formula 1c. The synthesis route is as follows:

[0011]

[0012] Compared with the prior art, the present invention develops a non-metal-doped porous tubular carbon nitride for the selective photocatalytic oxidation of sulfide compounds to sulfoxides, which effectively avoids the use of precious metals, electricity, and thermal energy, greatly reduces costs, simplifies the operating steps, and successfully obtains sulfone compounds with a yield of 90.7% under mild conditions, which provides a novel idea for the selective synthesis of sulfone compounds.

[0013] Furthermore, the amount of the boron-doped porous tubular carbon nitride is 0 to 50 mg.

[0014] Furthermore, the organic solvent is methanol, and the dosage is 0-3 ml.

[0015] Furthermore, the synthesis atmosphere is one of air, oxygen and argon, which saves synthesis time and ensures yield.

[0016] Furthermore, the synthesis time is 0 to 24 hours.

[0017] Furthermore, the lighting condition is within the visible light range.

[0018] Furthermore, the light is blue light 420nm.

[0019] Furthermore, B-doped porous tubular carbon nitride was used as a photocatalyst to achieve efficient synthesis of sulfide compounds into sulfone compounds through photocatalytic oxidation. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The screening bar graph of carbon nitride-based photocatalysts is (a) porous tubular modified carbon nitride photocatalyst, (b) porous tubular modified carbon nitride photocatalyst doped with different amounts of boric acid;

[0021] Figure 2 is a bar graph of the amount of B-doped porous tubular carbon nitride screened;

[0022] Figure 3 It is a bar chart of screening with different solvent amounts;

[0023] Figure 4 is a screening histogram of the reaction atmosphere;

[0024] Figure 5 is a screening histogram of reaction time;

[0025] Figure 6 It is a bar chart of different solvent screening;

[0026] Figure 7 It is a bar chart of different light source screening;

[0027] Figure 8 It is a screening bar chart of synergistic catalysts;

[0028] Fig. 9 It is the Na2S2O8 dosage screening bar chart;

[0029] Fig.10 It is the B-HTs-400 dosage screening bar chart;

[0030] Fig.11 is a screening histogram of reaction time;

[0031] Fig.12 is a screening bar chart of methanol usage;

[0032] Fig.13 It is a bar chart of different solvent screening;

[0033] Fig.14 It is a bar chart of different reaction atmospheres and dark reaction screening;

[0034] Fig.15 It is the bar graph of the cycle performance of B-HTs-400;

[0035] Fig.16 is the infrared spectra of B-HTs-400 before and after cycling;

[0036] Fig.17 are the SEM images of B-HTs-400 (a) before cycling, (b) after cycling, and (c) after heat treatment;

[0037] Fig.18 The free radical capture (EPR) spectra of B-HTs-400 are (a) holes, (b) superoxide radicals, (c) singlet oxygen, (d) sulfate radicals in oxygen atmosphere, (e) sulfate radicals in argon atmosphere, (f) comparison of sulfate radicals in oxygen and argon atmospheres;

[0038] Fig.19 is the isotope-labeled GC-MS graph of the B-HTs-400 catalytic reaction;

[0039] Fig. 20 is the cyclic voltammetry spectrum of B-HTs-400;

[0040] Fig.21 This is the preparation process of B-HTs-400. DETAILED DESCRIPTION

[0041] The following is a further detailed description through specific implementation methods:

[0042] Example 1.1

[0043] 20 mg of different carbon nitrides were placed in a 20 mL reaction tube, 1 mL of methanol solution was added, and methyl phenyl sulfide (1a, 37.2 mg, 0.3 mmol) was added to the solution using a pipette. The reaction tube was placed in a photoreactor, the appropriate speed was set, and the temperature of the condensation circulation pump was set to 20-25 ° C in the air for 12 hours as the initial reaction conditions. On this basis, the carbon nitride-based photocatalysts were first screened ( Figure 1 ), the results show that carbon nitride-based photocatalysts with element doping, morphology changes and defect structures have stronger catalytic ability. It is speculated that the changed morphology surface is distributed with many pore structures of different sizes, exposing more binding sites on the material surface. In addition, the doping of B element changes the local surface potential or morphological structure of the porous tubular carbon nitride, which effectively reduces the recombination rate between holes and photogenerated electrons.

[0044] Example 1.2

[0045] Based on the use of B-HTs-400 in Example 1.1, different amounts of B-HTs-400 (0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 mg) were screened ( Figure 2 ), the results showed that when no catalyst was used, the yield of the product was only 12%. It is worth noting that when there was no photocatalytic material in the catalytic system, the yield of the product was only 12.27%. However, when B-HTs-400 was added, the yield was significantly improved, proving that B-HTs-400 plays an important role in promoting the catalytic efficiency of the reaction. As the amount of material was added, the yield rose steadily and reached the optimal value at 15 mg, after which its yield did not fluctuate much. We speculate that the reason why the yield remained unchanged when more catalyst was used is that when 15 mg of catalyst was added, the substrate was almost completely reacted. Taking all factors into consideration, 15 mg was selected as the optimal catalyst dosage for the selective oxidation reaction of sulfide compounds catalyzed by B-HTs-400.

[0046] Example 1.3

[0047] Based on the amount of B-HTs-400 used in Example 1.2, different amounts of methanol (0, 0.5, 1, 1.5, 2, 2.5, 3 mL) were screened ( Figure 3 ), the results showed that the yield could reach 74% when the amount of methanol was 0.5 mL. It is worth noting that the yield could reach 44.60% under solvent-free conditions. However, with the increase of solvent, the yield decreased, which may be due to the combined factors of the decrease in substrate concentration, the degree of dispersion of the material and the stirring speed.

[0048] Example 1.4

[0049] Based on the amount of methanol used in Example 1.3, different reaction atmospheres (air, O2, Ar) were screened ( Figure 4 ), the results show that oxygen is a necessary condition for the reaction and is the oxygen source of sulfoxide. Longer reaction time will lead to further oxidation of sulfoxide. Therefore, we selected oxygen as the preferred atmosphere for the reaction, and the target product can be obtained in a shorter time.

[0050] Example 1.5

[0051] Based on the reaction atmosphere in Example 1.4, different reaction times (1, 2, 2.5, 3, 4, 6, 8, 10, 12, 24, 36 h) were screened. Figure 5 ), the experimental results show that the reaction is basically completed in about 2.5h under oxygen atmosphere, and the chemical selectivity is as high as 100%. As time increases, methyl phenyl sulfide is over-oxidized to generate methyl phenyl sulfone, resulting in a decrease in its chemical selectivity. We can obtain the product methyl phenyl sulfoxide with high selectivity by regulating the reaction time, and determine the reaction time to be 2.5h.

[0052] Example 1.6

[0053] Based on the reaction time in Example 1.5, the reaction solvent (organic solvent, water) was screened ( Figure 6). We screened the commonly used polar aprotic solvents, polar protic solvents and non-polar solvents. When polar aprotic solvents and non-polar solvents were used, the reaction was not ideal. However, a moderate yield can be obtained in acetonitrile solution. It is speculated that the viscosity coefficient of the screened polar aprotic solvent is so large that the catalytic material cannot be well dispersed in the solvent, reducing the probability of interfacial contact between the substrate and the material; while acetonitrile, as a polar aprotic solvent, has a viscosity that is no different from that of a polar protic solvent, and the catalytic material can be well dispersed, so a moderate yield can be obtained. The reason for the unsatisfactory yield of non-polar solvents may be that there is no participation of hydrogen donors in the reaction process, and the holes and photogenerated electrons of the catalytic material cannot be effectively separated, which in turn affects the generated active oxygen species and cannot be further converted, resulting in low yields. When polar protic solvents are used, the yield can reach a moderate to excellent yield. This is because the catalytic material not only has good dispersibility in such solvents, but the solution itself can also serve as a hydrogen donor. Because the energy required for the hydrogen donors produced by different protic solvents is different, the yields obtained by catalysis are different. Surprisingly, water, a protic solvent similar to alcohol, only detected a yield of 20.64%. We speculate that the reason for this phenomenon may be that B-HTs-400, as an organic semiconductor, has a hydrophobic surface. In addition, the substrate, as an organic matter, cannot be effectively dissolved in water. Therefore, under the combined influence of these factors, the yield of water as a solvent is greatly reduced. Finally, we selected methanol as the best reaction solvent.

[0054] Example 1.7

[0055] Based on the reaction solvent in Example 1.6, the reaction light source (visible light) was screened ( Figure 7 ). The results showed that a moderate yield could be obtained under visible light irradiation, while the catalytic reaction was best under blue light (420nm), and almost no reaction occurred under the standard reaction conditions under other light. It is worth noting that a small amount of product could be detected when the reaction time was extended by one and a half hours under red light.

[0056] Example 2.1

[0057] 20 mg B-HTs-400 was placed in a 20 mL reaction tube, 1 mL methanol solution was added, and methyl phenyl sulfide (1a, 37.2 mg, 0.3 mmol) was added to the solution using a pipette. The reaction tube was placed in a photoreactor, the appropriate speed was set, and the temperature of the condensation circulation pump was set to 20-25 ° C in the air for 12 h as the initial reaction conditions. On this basis, different synergistic catalysts (persulfide, carbonate, etc.) were first screened ( Figure 8), the results showed that in the screening of multiple synergistic catalysts, sodium chlorite, phosphorus pentoxide, sodium persulfate and potassium persulfate had good potential in synergistic catalysis. Then, we conducted a preliminary experiment on sodium chlorite and found that the oxidation capacity was significantly improved after adding several times the equivalent of sodium chlorite, but this would introduce a large amount of halogen, which is not friendly to the environment and violates the concept of sustainable development. Therefore, the corresponding equivalent reagents were pre-experimented on the remaining three reagents, and the experimental results of sodium persulfate aroused our interest.

[0058] Example 2.2

[0059] Based on the use of Na2S2O8 in Example 2.1, the equivalents of Na2S2O8 (0, 0.5, 1, 1.5, 2, 2.5, 3) were screened ( Fig. 9 ), the results show that with the increase of sodium persulfate, the yield of 1b gradually decreases while the yield of 1c increases synchronously, proving that the oxidation process of thioether is carried out step by step. When 2.5eq. of sodium persulfate is added, the target product can be obtained with an excellent yield (79.38%), and its chemical selectivity reaches 100.00%. Continuing to increase the input of sodium persulfate, the yield does not increase significantly, but decreases. This may be caused by the high oxidative activity (sulfate radical) generated by excessive sodium persulfate oxidizing and decomposing part of the product. Therefore, the amount of sodium persulfate was determined to be 2.5eq.

[0060] Example 2.3

[0061] Based on the Na2S2O8 equivalent in Example 2.2, the dosage of B-HTs-400 (0, 5, 10, 15, 20, 25, 30 mg) was screened ( Fig.10 ), the results show that without the synergistic effect of photocatalytic materials, almost no over-oxidation products are generated, and only a small amount of 1b is generated, which proves that the synergistic effect of materials and sodium persulfate is very important in this system. When the material dosage is 10 mg, the target product 1c can be selectively generated, and the obtained yield can reach 82.29%. With the increase of material, the target yield did not increase as expected, but fluctuated slightly up and down. Therefore, considering the cost issue, we chose the material dosage of 10 mg.

[0062] Example 2.4

[0063] Based on the dosage of B-HTs-400 in Example 2.3, different reaction times (1, 2, 3, 4, 5, 6, 7, 8, 9, 10 h) were screened. Fig.11), with the extension of reaction time, the selectivity and yield of 1c showed an upward trend. When the reaction time was 8 h, the substrate was almost converted and the target product with high selectivity was obtained. Further extension of the reaction time did not significantly improve the yield and selectivity of the target product. Therefore, we determined that the optimal time for the catalytic reaction was 8 h.

[0064] Example 2.5

[0065] Based on the reaction time in Example 2.4, the amount of methanol (0, 0.5, 1, 1.5, 2, 2.5 mL) was screened ( Fig.12 It is worth noting that the yield of the target product under solvent-free conditions is as high as 14.70%, proving that interfacial catalysis is one of the important modes of the catalytic process. Among them, since the yield and chemical selectivity of 1c did not increase with the increase of solvent, we determined the amount of reaction solvent to be 1 mL.

[0066] Example 2.6

[0067] Based on the amount of methanol used in Example 2.5, the reaction solvents (organic solvents, water and alcohol-water mixed solutions) were screened ( Fig.13 ). The results show that we screened the commonly used polar aprotic solvents (, polar protic solvents and non-polar solvents. From the analysis of experimental data, polar aprotic solvents can obtain moderate to excellent yields. It may be that the solubility of sodium persulfate in such solvents is high, which promotes the synergistic catalysis. It is speculated that the active substances for the further oxidation of thioethers mainly come from the generation of sodium persulfate; alcohol solvents in polar protic solvents are quenchers of most transient free radicals such as (methanol-hydroxyl radicals, ethanol-sulfate radicals, tert-butanol-superoxide radicals, etc.), which leads to a decrease in the target yield. This phenomenon shows that the oxidation process of thioether-sulfone in this system is the result of a combination of multiple factors; the addition of solvent water reduces the dispersibility of the material in the solvent, inhibits the interfacial catalytic process and reduces the yield; non-polar solvents not only have low dielectric constants but also have poor solubility for sodium persulfate, so they are greatly restricted in the process of generating oxidative active substances. Therefore, the yield of 1c is also low. Finally, we chose methanol as the reaction solvent.

[0068] Example 2.7

[0069] Based on the reaction solvent in Example 2.6, Fig.14 The reaction atmosphere (air, O2, Ar) and dark reaction were screened. The data showed that oxygen atmosphere is no longer an indispensable factor in this reaction system, but the addition of oxygen can effectively promote the catalytic rate. In addition, the reaction hardly occurs under dark conditions, proving that light is very important.

[0070] Example 8

[0071] Based on Example 2.7, the catalytic performance of B-HTs-400 was examined. Fig.15 This is a bar chart of the cycle performance of B-HTs-400. The data shows that the catalytic performance of the catalyst will decrease after one cycle. When we cycle for eight times, the yield is stable between 60-70%. We restore the activity of the catalyst by heat treatment. Repeated heat treatment does not reduce the catalytic performance of the catalyst, and it can be cycled at least ten times. Therefore, the catalyst has good cycle stability.

[0072] Example 9

[0073] Fig.16 The infrared spectra of B-HTs-400 before and after the cycle are shown in the Fourier infrared spectrum. It can be clearly seen that compared with B-HTs-400 before the reaction, the photocatalytic material after the cycle and heat treatment only has a new and weak characteristic peak at 1000-1110cm-1, which is attributed to the stretching vibration of S=O, and the characteristic peak of CSC is around 830cm-1, but it is covered by the characteristic peak of the triazine ring system of the catalyst, which is consistent with the results of the element content analysis, and is conducive to confirming the adsorption effect of the material and the view of interface catalysis. At the same time, it further illustrates that the temperature of the heat treatment does not change the most basic structure of the catalytic material, and it has strong thermal stability.

[0074] Example 10

[0075] Fig.17 The SEM and TEM images of B-HTs-400 before and after cycling and heat treatment. The catalyst after cycling is no longer porous tubular, and its regular three-dimensional structure has been destroyed during the reaction. The catalyst that recovered its activity after heat treatment did not undergo significant changes in microstructure compared to the passivated catalyst, but many protrusions were exposed in the destroyed three-dimensional structure. The appearance of these protrusions may be the basis for the catalyst to maintain cycling stability. It was found that the element comparison before and after cycling showed that there was more sulfur, which indicates that the catalyst has an adsorption effect on the substrate or product, and there may be an interfacial catalytic method. In particular, there was no crystal phase transition before and after cycling and before and after heat treatment through HRTEM images and electron diffraction images, and it has always been amorphous. This proves that the chemical properties of the catalyst itself are very stable during the reaction, and the heat treatment process only removes the attached reactants.

[0076] Embodiment 11

[0077] Fig.18This is the free radical capture diagram of B-HTs-400. To determine the presence of holes, superoxide radicals, singlet oxygen and sulfate radicals, we conducted EPR tests, and the data showed the presence of the above active oxidizing species. It is worth noting that under the same test conditions, the sulfate signal in oxygen atmosphere is stronger than that in argon atmosphere, which is one of the reasons why the catalytic yield of sulfide oxidation to sulfone in argon atmosphere is low under the same reaction conditions.

[0078] Example 12

[0079] Fig.19 In order to analyze the oxygen source of the oxidation products catalyzed by B-HTs-400, oxygen isotope labeling experiments were carried out. The data showed that the oxygen source of sulfoxide was oxygen, and the oxygen source of sulfone was partly derived from oxygen and partly from persulfide.

[0080] Embodiment 13

[0081] Fig. 20 The cyclic voltammogram of B-HTs-400 shows clearly that there is no redox peak in the absence of catalytic materials, nitrogen atmosphere and air conditions. It is worth noting that a relatively obvious reduction peak appears when oxygen is introduced during the test. Therefore, we speculate that B-HTs-400 has a certain reducing property to oxygen, which further proves that superoxide radicals may originate from the reduction of oxygen. In addition, when we introduced light, we found that not only there was a reduction peak in air and oxygen atmosphere, but also the value of its reduction potential increased. This shows that light may cause the catalyst to generate photogenerated electrons and holes, greatly improving the photocatalytic performance of B-HTs-400.

[0082] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds, characterized in that: The methyl phenyl sulfide shown in formula 1a is used as a substrate, porous tubular carbon nitride (B-HTs-400) is used as a photocatalyst, and any one or two of an organic solvent and water are used as reaction solvents to synthesize the methyl phenyl sulfoxide shown in formula 1b. The synthesis route is as follows:

2. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 1, characterized in that: The porous tubular carbon nitride is boron-doped porous tubular carbon nitride (B-HTs-400).

3. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 2, characterized in that: The invention also includes a synergistic catalyst, which is sodium sulfate, and the amount used is 0 to 5 eq. The methyl phenyl sulfone shown in the synthetic formula 1c is as follows:

4. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 3, characterized in that: The amount of the boron-doped porous tubular carbon nitride is 0 to 50 mg.

5. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 4, characterized in that: The amount of sodium sulfate used is 0 to 5 eq.

6. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 1 or 5, characterized in that: The organic solvent is methanol, and the dosage is 0-3 ml.

7. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 6, characterized in that: The synthesis atmosphere is one of air, oxygen and argon.

8. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 7, characterized in that: The synthesis time is 0 to 24 hours.

9. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 8, characterized in that: The illumination condition is within the visible light range.

10. The method for selective photocatalytic oxidation of sulfide compounds to sulfone compounds according to claim 9, characterized in that: The light is blue light 420mm.

Citation Information

Cited By

  • A method for synthesizing a beta-arylthio amide compound

    CN122627956A